รูปแบบการบริหารจัดการงานวิจัยเพื่อการหนุนเสริมงานวิจัยเพื่อท้องถิ่นของมหาวิทยาลัยอุบลราชธานี - เลียงจินดาถาวร อรทัย; สำนวนเย็น กิ่งกาญจน์; อันพิมพ์ อุทัย; บุญดาว รุ่งรัศมี; ศุภดล ปัญจีรา; สุตัญตั้งใจ นาวินี (Area Based Development Research Journal, 2016)
งานวิจัยนี้ มีวัตถุประสงค์เพื่อศึกษาสถานการณ์และกระบวนการบริหารจัดการงานวิจัยเพื่อท้องถิ่นของมหาวิทยาลัยอุบลราชธานี ในระดับคณะและระดับมหาวิทยาลัย โดยศึกษาปัจจัยที่เอื้อและเป็นอุปสรรคต่อการพัฒนากลไกสําหรับการจัดตั้งและบริหารจัดการประชาคมวิจัยเพื่อท้องถิ่นของมหาวิทยาลัย ค้นหารูปแบบในการบริหารจัดการประชาคมวิจัยเพื่อท้องถิ่น และค้นหารูปแบบการหนุนเสริมงานวิจัยเพื่อท้องถิ่นของมหาวิทยาลัยอุบลราชธานี การวิจัยใช้วิธีวิทยาการวิจัยเชิงปฏิบัติการแบบมีส่วนร่วม (Participatory action research) ผู้ให้ข้อมูล ได้แก่ ผู้บริหารและเจ้าหน้าที่สํานักงานส่งเสริมบริหารงานวิจัย บริการวิชาการและทํานุบํารุงศิลปวัฒนธรรม มหาวิทยาลัยอุบลราชธานี ผู้บริหารและเจ้าหน้าที่ปฏิบัติงานวิจัยของคณะ จํานวน 10 คณะ และ 1 วิทยาลัย Node นักวิชาการของสํานักงานกองทุนสนับสนุนการวิจัย (สกว.) เครือข่ายนักวิจัยเพื่อท้องถิ่นของมหาวิทยาลัยอุบลราชธานี นักวิจัยที่ได้รับการสนับสนุนทุนวิจัยเพื่อท้องถิ่น ปี พ.ศ. 2556 และนักวิจัยชุมชน จํานวน 6 โครงการ เก็บรวบรวมข้อมูลด้วยการสัมภาษณ์เชิงลึก การสนทนากลุ่ม การประชุมและการจัดอบรมเชิงปฏิบัติการ และการทดลองปฏิบัติการบริหารจัดการงานวิจัยเพื่อท้องถิ่น และหนุนเสริมนักวิจัยเพื่อท้องถิ่นในรูปแบบประชาคมวิจัยกับโครงการที่ได้รับทุนวิจัยเพื่อท้องถิ่น ปี พ.ศ. 2556 จํานวน 6 โครงการ ผลการวิจัย พบว่า รูปแบบการบริหารจัดการประชาคมวิจัยเพื่อท้องถิ่นของมหาวิทยาลัยอุบลราชธานี ควรมีองค์กรในการบริหารจัดการงานวิจัยเพื่อท้องถิ่นที่ชัดเจน กําหนดระบบการบริหารจัดการงานวิจัยเพื่อท้องถิ่น ให้สอดคล้องกับแนวคิดการวิจัยเพื่อท้องถิ่น หลักเกณฑ์ และกระบวนการบริหารจัดการของแหล่งทุน โดยยึดหลักการมีส่วนร่วมของผู้ที่เกี่ยวข้องตลอดทั้งกระบวนการ ส่วนการหนุนเสริมงานวิจัยเพื่อท้องถิ่นในรูปแบบประชาคมวิจัย ควรประกอบด้วย การสนับสนุนทุนวิจัยเพื่อท้องถิ่น การสนับสนุนของสํานักส่งเสริมและบริหารงานวิจัยฯ การหนุนเสริมของพี่เลี้ยง และการหนุนเสริมการพัฒนานักวิจัยเพื่อท้องถิ่น Pattern of Research Management to Support and Enhance Community Based Research of Ubon Ratchathani University This research aims to study the situation and managing process of community based research, both in faculty and institution levels, of Ubon Ratchathani University. Both supportive and obstructive factors to the development of procedures for setting up and managing community based research as well as the patterns to manage and support the research were investigated. This research was conducted by participatory action research methodology. The informants were 1) executives and staff of the Office of research, Academic Services, and Art & Cultural Preservation of Ubon Ratchathani University, 2) executives and research staff of 10 faculties and 1 college, 3) academic officers of the Thailand Research Fund (TRF), 4) the network of researchers in community based research of Ubon Ratchathani University, 5) researchers with scholarships on community based research in 2013, and 6) community researchers from 6 projects. Information collected by in-depth interviews, group discussions, workshops, and operational experimentation to manage community based research and to promote a network of research community, cooperated with 6 projects funded in 2013 to conduct the community based research. The results has suggested that the management should have a clear and specific organization to manage the research. The systems of management to conform with the concept of community based research include the regulations and management based on the principle of participation of all relevant personals throughout the process. The support of community based research of the university should comprise the scholarship to support community based research, the support from the Office of research, Academic Services, and Art & Cultural Preservation, the support from mentors, and the promotion of researchers on community based research.